Variability in contamination of submarine groundwater discharge into West Hawai‘i coral reefs - Hondula, Kelly L.; Martin, Roberta E.; Asner, Gregory P. (Frontiers in Marine Science, 2025)
Sewage pollution is a global threat to coastal ecosystems and amplifies the negative effects of climate change on coral reefs. Submarine groundwater discharge (SGD) is a major transport pathway for land-based pollution, but underlying drivers of SGD water quality are poorly understood, especially in nearshore coral reef ecosystems. We combined airborne mapping, field sampling, and statistical modeling to identify locations along the West Hawai‘i Island coastline where SGD is contaminated with sewage. Water samples collected from 47 distributed shoreline SGD locations were assayed for fecal indicator bacteria. A geostatistical model was used scale from field to regional levels at more than 1000 mapped SGD point locations to derive a geographic understanding of areas highly susceptible to contamination. We estimate that SGD delivers sewage-contaminated groundwater to at least 42% of reefs in West Hawaiʻi. Subsequent analyses indicate that contaminated points are associated with infrastructural build-up near the shoreline and an abundance of inland on-site sewage disposal systems. Mitigation of sewage pollution will require the prevention of numerous point sources from cesspools, septic leach fields, and similar sources.